DATA-SURVEY: Migrant Acceptance Index: A Global Examination of the Relationship Between Interpersonal Contact and Attitudes toward Migrants - Fleming, John H.; Esipova, Neli; Pugliese, Anita; Ray, Julie; Srinivasan, Rajesh (Border Crossing, 2018)
Using independently sampled Gallup World Poll survey data from 140 countries, we explored the relationship between interpersonal contact and attitudes toward migrants from a perspective not typically found in the social psychological literature. We hypothesized that respondents who report personally knowing a migrant living in their home country would be more accepting of migrants generally (using a three-item Migrant Acceptance Index (MAI) score) than respondents who do not know a migrant. Results supported our hypothesis in 134 of the 140 countries suggesting that the strong relationship between interpersonal contact and attitudes toward migrants is near-universal. We also quantified migrant acceptance at the country level, finding a wide spectrum of attitudes toward migrants. Low acceptance countries were located primarily in Eastern and Southeastern Europe and high acceptance countries were located in Northern Europe and sub-Saharan Africa. We discuss these results in the context of interpersonal contact theory (Allport, 1954) and the larger context of global migration.